Edukasi Vaksinasi COVID-19 Dosis Ketiga (Booster): Tak Kenal Maka Tak Kebal - Raja Fitrina Lestari; Susi Erianti; Ennimay Ennimay (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
The spread of covid-19 in indonesia is on the rise. the provision of a covid-19 vaccine from the government is still one of the efforts to prevent and control the transmission of the covid-19 disease. the government continues to intensify the implementation of the covid-19 vaccine, especially the third dose of covid-19 vaccine (booster) for eligible indonesians. the purpose of this community service is to provide an understanding of the third dose of covid-19 vaccination (booster) with the lecture method of distributing flyer, leaflet containing knowledge about the third dose of vaccination (booster). in this activity, a total of those who have undergone the third dose of covid-19 vaccination (booster) starting from the leadership and employees of pt. lingga cargo as many as 7 employees (25%) of the 28 employees. the next hope is to continue to strive to accelerate the third dose of covid-19 vaccination (booster) program by providing education related to vaccination and collaborating with related parties both across programs and across sectors and also reminding the public to continue to follow the health protocol even though they get the third dose of vaccine. vaccination is one of the important components in the pandemic handling strategy to reduce the risk of severe illness and death from covid-19.